Efficacy of ivermectin against colon cancer induced by dimethylhydrazine in male wistar rats - Hamzah A. Alghamdi; Mohammed Al-Zharani; Nada H. Aljarba; Abdullah A. Alghamdi; Abdulrahman A. Alghamdi; Badr A. Aldahmash; Doaa M. Elnagar; Saad Alkahtani (Saudi Pharmaceutical Journal, 2022)
Colon cancer (CC) is a common form of cancer worldwide. According to growing incidence of cancer and little information about the possible protective role of Ivermectin (IVM) on colon cancer, this study aimed to investigate the chemoprotective role of IVM against colon cancer induced by Dimethylhydrazine (DMH) in Male Wistar Rats. Based on LD50, three doses of IVM (0.25, 0.5, and 1 mg/kg) were applied before assayingthe antioxidant status, apoptotic markers, and microscopic analysis. Our result showed that glutathione (GSH) level was significantly increased in low dose of IVM-treated rats. Hight levels of oxidative stress and tissue damage consumed GSH and catalase (CAT), and dismutase (SOD) as indicated by significant drop in the treated groups. mRNA levels of Bax and caspase-3 were upregulated in rats treated with the high dose. Contrastingly, the expression of Bcl-2 was significantly downregulated with high dose. Changes in genes expression proved that IVM triggered apoptosis in treated groups compared to untreated control group. Microscopic analysis showed that rats treated with DMH exhibited high development of colorectal tumor. After induction of colorectal tumor, medium and high dose of DMH induced reduction in medullary carcinoma with great incidence of lymphoid nodules and desmoplastic reaction. In conclusion, this study demonstrates the potential of IVM as an anticancer drug against colon cancer in male Wistar rats.